2014
DOI: 10.1371/journal.pone.0103644
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Pathological Mutations and Proline Substitutions in TDP-43 Glycine-Rich Peptides on Its Amyloid Properties and Cellular Toxicity

Abstract: TAR DNA-binding protein (TDP-43) was identified as the major ubiquitinated component deposited in the inclusion bodies in amyotrophic lateral sclerosis (ALS) and frontotemporal lobar degeneration with ubiquitin-positive inclusions (FTLD-U) in 2006. Later on, numerous ALS-related mutations were found in either the glycine or glutamine/asparagine-rich region on the TDP-43 C-terminus, which hinted on the importance of mutations on the disease pathogenesis. However, how the structural conversion was influenced by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 47 publications
1
27
0
Order By: Relevance
“…10. Our sequence 274 -353 overlaps well with those reported by Huang and co-workers (28,29), although other sequences were not identified in this study. The discrepancy may be due to the difference in the length of peptides used in in vitro aggregate formation assay (we prepared 40-mers in contrast with their short 8 -12-mer peptides).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…10. Our sequence 274 -353 overlaps well with those reported by Huang and co-workers (28,29), although other sequences were not identified in this study. The discrepancy may be due to the difference in the length of peptides used in in vitro aggregate formation assay (we prepared 40-mers in contrast with their short 8 -12-mer peptides).…”
Section: Discussionsupporting
confidence: 90%
“…Huang and co-workers (28,29) showed that peptides in the sequence (287-322) have a propensity for aggregation, and this tendency was altered by substitution of glycines with prolines. The sequences reported in previous studies and identified in this study are summarized in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…While electron microscopy studies have revealed the formation of amorphous aggregates, the low fluorescence intensity after incubation with Thioflavin T (ThT) confirmed that GGG308PPP could not form fibrils. [11] These experiments suggest that the glycines 308-310 are required for both membrane disruption and fibril formation of D1 (Supporting Information, Table S1). …”
mentioning
confidence: 99%
“…Huang et al have shown that D1 peptides form pores in lipid membranes that are sufficiently large to allow leakage of calcein (MW % 620 Da) from large unilamellar vesicles. [11] In contrast, the GGG308PPP mutant does not form membrane pores. While electron microscopy studies have revealed the formation of amorphous aggregates, the low fluorescence intensity after incubation with Thioflavin T (ThT) confirmed that GGG308PPP could not form fibrils.…”
mentioning
confidence: 99%
See 1 more Smart Citation